Understanding human behavior in the light of Prophet's life - Dr. Shabana Rashed Anjum (Al Manhal Research Journal, 2024)
The Prophet's biography is a source of guidance for humanity, guiding them in all aspects of life. By the order of the Messenger of Allah, he explained all the ways by which a person can enter the spiritual realm even while living in the material world and can make himself the vicegerent of God Almighty on earth. However, in order to achieve this position and status, it is necessary that a person not only for himself but also be useful to others. of ۔each person with others in this rage. Behavior matter from a psychological point of view, people with positive thought patterns and resilient behavior are more beneficial to society. However, no single theory of psychology can fully explain how such behaviors occur. Because today the reality is that we are human beings It is getting free from relationships and relationships. On the other hand, when someone's teachings of the Messenger of Allah, peace and blessings be upon him And if one contemplates the biography, one will find such gems that can foster close ties of family relationships. Communication is the main mode of expression of human behavior. If during the conversation If the Muslims of today follow the teachings of Rasulullah sallallaahu alayhi wa sallam Relationships can be preserved, as the Prophet (PBUH) condemned lying, backbiting and idle talk, and sanctioned meetings with others. Advised not to prolong the necessary conversation. In the same way, all relationships such as "parents, parents, siblings, spouses, children." How should one behave with neighbors and relatives and even children? All this only and only from the life of the Prophet (PBUH). Can be learned. Not only this, but by understanding the life of the Holy Prophet (PBUH), the ruler, military leader and religious leader will achieve success and progress.